Successes and failures of conflict governance: Lessons from Aceh, Indonesia and Moro, Philippines - Badu, Muhammad Nasir; Syafhendry, Syafhendry; Tenorio, Christine B. (Otoritas : Jurnal Ilmu Pemerintahan, 2023)
The purpose of this study is to analyze ethnic conflict management in Aceh (Indonesia) and Moro (Philippines) conflicts. The Aceh conflict was considered resolved after the signing of the Helsinki agreement, which was mediated by the Crisis Management Initiative (CMI), an international NGO based in Finland, on 15 August 2005 between Indonesian government and the Free Aceh Movement (Gerakan Aceh Merdeka, GAM). Meanwhile, the Moro (Philippines) conflict is still ongoing despite the TRIPOLI agreement signed and mediated by the OIC (Organization of Islamic Conference) between the Philippine government and the Moro National Liberation Front (MNLF) on 23 December 1976 and also with the MILF in 2001. This research method uses a qualitative approach. Primary data was obtained through interviews with figures who were considered competent in the Aceh conflict and the Moro conflict. The results of this study show that CMI in Aceh has succeeded in changing the situation of ethnic conflict into a situation that can reduce and reduce escalation and direct conflict actors towards conflict resolution. Peacemaking, peacekeeping and peace building have been played well by CMI involving the international community such as ASEAN and the European Union to manage the conflict. Meanwhile, in Moro the OIC failed to bring the conflict actors to solve their problems. The Philippine government lacks a robust vision, framework, and the necessary political will to effectively address the Moro conflict, which is of concern to the Organization of Islamic Cooperation (OIC).